Augmented Reality (AR) Integration in STEM Learning: An Experimental Study on Students with Special Needs - Arsyad, Muhammad; Apriansyah, Deni; Awaludin, Dipa Teruna; Khasanah, Khasanah; Prasetyo, Pardan (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This research examines the incorporation of Augmented Reality (AR) technology into STEM (Science, Technology, Engineering, and Mathematics) educational settings tailored for students with special needs. It seeks to assess the efficacy of AR-driven instructional tools in bolstering conceptual comprehension, learner involvement, and intrinsic motivation among individuals facing varied cognitive and physical impairments. The methodology utilized an experimental framework, contrasting an intervention cohort exposed to AR-augmented STEM curricula against a comparison cohort subjected to traditional teaching methods. Information was gathered via initial and follow-up evaluations, observational records, and participant response surveys. Findings indicated that the intervention cohort achieved markedly superior educational results and displayed elevated participation and enthusiasm relative to the comparison group. These outcomes underscore AR's role as an equitable pedagogical resource that facilitates multimodal learning, aids in the representation of intangible STEM ideas, and ensures equitable access to education for students with special needs. The investigation concludes that embedding AR within inclusive STEM pedagogy offers substantial promise for nurturing intellectual and emotional growth, warranting additional inquiry into customizable AR frameworks designed to deliver individualized instructional assistance.